Review of the genus Amphinemura (Plecoptera: Nemouridae) from Guangdong, China - Li, Weihai; Yang, Ding (Zootaxa, 2007)
The species of the genus Amphinemura from Guangdong are reviewed and keyed. Three new species, Amphinemura ancistroidea sp. nov., Amphinemura filarmia sp. nov., and Amphinemura scalprata sp. nov., are described. Their relationships with related species are discussed.